Smart irrigation system with internet of things for rose cultivation in a basic greenhouse in Canchis, Cusco, 2025 - Benique, Marco Antonio Roque; Teves, Luis Enrique Falcon; Ortiz, Eduar Anibal Vasquez (Institute of Advanced Engineering and Science, 2025)
A large percentage of the world’s freshwater is allocated to agriculture, which presents a significant challenge for the future in light of a growing global population and climate change. In this context, it is essential to implement technologies that enable more efficient water resource management. Consequently, a smart irrigation system with internet of things (IoT) was developed for rose cultivation in a basic greenhouse located in Canchis, in the Cusco region, in 2025. This project integrated sensors for data acquisition, ESP32 modules for control, and solenoid valves as actuators. Additionally, the ThingSpeak platform was used for monitoring. The implementation of the system in the basic greenhouse demonstrated reliable communication between the different nodes and the virtual platform, as well as full automation through the solenoid valve’s response to a defined threshold. Finally, it showed an average water consumption savings per irrigation of up to 46.26% compared to the previous system.